2013
DOI: 10.1002/ase.1377
|View full text |Cite
|
Sign up to set email alerts
|

The perceived importance of anatomy and neuroanatomy in the practice of speech—Language pathology

Abstract: The purpose of this study was to examine the application of anatomy and neuroanatomy knowledge to current practice of speech-language pathology (SLP), based on the perceptions of practicing SLPs, and to elicit information on participants' experiences of learning these subjects in their primary SLP degree with a view to inform potential curriculum development. A qualitative approach was taken to the collection of data. Eight practicing SLPs from four settings were interviewed. The critical incident technique, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Such causal factors have been investigated but were limited in the level of inquiry to broad topics and in their representation of student cohorts. Several investigators addressed medical students only (Schon et al, ; Flanagan et al, ; Ridsdale et al, ; Lim and Seet, ; Hudson, ; Youssef, ; Sanya et al, ; Zinchuk et al, ; Gupta et al, ; Kam et al, ; Matthias et al, ; McCarron et al, ; Pakpoor et al, ; Abushouk and Duc, ), while Martin et al () interviewed only speech and language therapy practitioners. Most of these studies focused on clinical neurology and alluded to an impaired understanding of neuroanatomy in the broader context of the difficulties associated with learning and practice of neurology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such causal factors have been investigated but were limited in the level of inquiry to broad topics and in their representation of student cohorts. Several investigators addressed medical students only (Schon et al, ; Flanagan et al, ; Ridsdale et al, ; Lim and Seet, ; Hudson, ; Youssef, ; Sanya et al, ; Zinchuk et al, ; Gupta et al, ; Kam et al, ; Matthias et al, ; McCarron et al, ; Pakpoor et al, ; Abushouk and Duc, ), while Martin et al () interviewed only speech and language therapy practitioners. Most of these studies focused on clinical neurology and alluded to an impaired understanding of neuroanatomy in the broader context of the difficulties associated with learning and practice of neurology.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed a lower retention of neuroanatomical knowledge compared to physiology and immunology, re‐affirming the difficult nature of the subject. Similarly, in face‐to‐face interviews practicing speech and language therapists specifically labeled their experience of learning neuroanatomy from textbooks and traditional lectures as “very, very hard and tough,” especially compared to other disciplines (Martin et al, ). Overall, neuroanatomy is consistently cited as one of the most challenging portions of the anatomical sciences curriculum by medical students and junior physicians alike (Jilwan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although gross anatomy laboratory exercises are often not compulsory in Speech and Language Therapy programs, the importance of interacting directly with a prosected human specimen is recognized as beneficial by speech and language pathology students (Weir, ; Skinder‐Meredith, ; Martin et al, ). Therefore, examining cadaveric prosections can be an important adjunct to the academic progress and future clinical knowledge of students taking part in this experience.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence has been reported globally, in countries including Ireland and the United Kingdom (Flanagan et al, ; McCarron et al, ; Pakpoor et al, ; Conway and Tubridy, ), the United States (Zinchuk et al, ; Mullally, ), Caribbean countries (Youssef, ), Nigeria (Sanya et al, ), Sri Lanka (Matthias et al, ), and Portugal (Arantes et al, ). In this context, studies have shown that the perception of neuroanatomy as a difficult subject is a significant contributor to the problem (Martin et al, ; Javaid et al, ). A recent survey has shown that medical and health sciences students rank the innate complexity of the topic, a lack of understanding of the clinical relevance of basic neuroanatomical facts, and the difficult visualization of the three‐dimensional inter‐relationship of neuroanatomical structures as the main reasons for their difficulty with neuroanatomy (Javaid et al, ).…”
Section: Introductionmentioning
confidence: 99%